ANALISIS KESESUAIAN ANTARA LATAR BELAKANG PENDIDIKAN GURU MADRASAH IBTIDAIYAH DENGAN MATA PELAJARAN YANG DIAMPU - Samsul Bahri (Jurnal Numeracy, 2019)
Teachers must have academic qualifications and educational backgrounds in accordance with the field of duty. The teacher as a professional means that the teacher's work can only be done by someone who has academic qualifications, competencies, and educator certificates in accordance with the requirements for certain types and levels of education. The objectives of the research in this study are: To what extent is the degree of conformity between the education background of the Madrasah ibididaiyah teachers and elementary schools in the North Aceh environment with the subjects taught. In this study using qualitative research. The conclusions were that there were 27.86% or as many as 102 out of 366 teachers who had educational backgrounds that were not in accordance with heresy skills. Many factors influence the teachers of madrasah ibtidaiyah and elementary schools in the North Aceh environment in teaching subjects are: "a) knowledge in terms of educational background relations with subjects taught; b) skills; c) ability (talent) and motivation; d) attitudes and responsibilities and e) behavior of the teachers in the school; f) teaching experience. Abstrak Guru harus memiliki kualifikasi akademik dan latar belakang pendidikan sesuai dengan bidang tugas. Guru sebagai tenaga profesional mengandung arti bahwa pekerjaan guru hanya dapat dilakukan oleh seseorang yang mempunyai kualifikasi akademik, kompetensi, dan sertifikat pendidik sesuai dengan persyaratan untuk setiap jenis dan jenjang pendidikan tertentu. Adapun yang menjadi tujuan penelitian dalam penelitian ini adalah: Sejauh mana tingkat kesesuaian latar belakang pendidikan guru madrasah ibdidaiyah dan sekolah dasar di lingkungan aceh utara dengan mata pelajaran yang diampu. Dalam penelitian ini menggunakan penelitian kualitataif. Adapun kesimpulan tersebut ada 27,86% atau sebanyak 102 dari 366 guru yang memiliki latar belakang pendidikan tidak sesuai dengan bidah keahlian. Banyak faktor yang mempengaruhi guru madrasah ibtidaiyah dan sekolah dasar di lingkunagn Aceh Utara dalam mengampu mata pelajaran adalah: “a) pengetahuan dalam artian relasi latar belakang pendidikan dengan mata pelajaran yang diajarkan; b) keterampilan; c) kemampuan (bakat) serta motivasi; d) sikap serta tanggung jawab dan e) perilaku dari para guru yang ada di dalam sekolah; f) pengalaman mengajar. Kata kunci: Latar Belakang Pendidikan, Mata Pelajaran yang Diampu